1997
DOI: 10.1002/(sici)1097-4628(19970222)63:8<1047::aid-app11>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

?Antiplasticization? in starch-glycerol films?

Abstract: Calorimetric, mechanical, and thermomechanical properties have been measured on starch films with various glycerol/water contents. For calorimetric measurements, a continuous decrease in T g was observed as glycerol increases from 0 to 25%. Mechanical properties exhibit a minimum of elongation at break for glycerol content Ç 12%. In slightly hydrated starch films not containing another plasticizer, a b relaxation is detected by DMTA around 068ЊC. This relaxation is modified by the presence of glycerol, the a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
2
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(106 citation statements)
references
References 6 publications
12
86
2
6
Order By: Relevance
“…This phenomenon also exists in TPS and has been receiving increasing attention recently (Chang et al, 2006). Contrary to the orthodox behaviour of plasticization, plasticizer can reduce elongation and gas permeability, and increase tensile strength and modulus of elasticity of TPS when it is introduced in low amount under a critical level (generally <25%) (Godbillot et al, 2006;Lourdin et al, 1997;Zhang & Han, 2010). Fig.…”
Section: Tps Antiplasticization and Its Explanationmentioning
confidence: 99%
“…This phenomenon also exists in TPS and has been receiving increasing attention recently (Chang et al, 2006). Contrary to the orthodox behaviour of plasticization, plasticizer can reduce elongation and gas permeability, and increase tensile strength and modulus of elasticity of TPS when it is introduced in low amount under a critical level (generally <25%) (Godbillot et al, 2006;Lourdin et al, 1997;Zhang & Han, 2010). Fig.…”
Section: Tps Antiplasticization and Its Explanationmentioning
confidence: 99%
“…This phenomenon was possibly related to the permanence of the grains in the water/ glycerol solution: indeed, glycerol is an efficient plasticizing agent that has a crucial influence on starch-based materials (28) and possibly enhanced the swelling of the grains that were previously subjected to thermal processing. Furthermore, observations carried out on starch grains from other ancient grinding stones indicated that the use of water/glycerol solution alone was not sufficient to cause jelling and swelling: indeed, the phenomenon was not observed in the Bilancino starch grains, which were subjected to the same laboratory procedure (3), after a prolonged permanence in the water/glycerol solution.…”
Section: Discussionmentioning
confidence: 99%
“…20% glycerol has been shown to be the maximum rate leading to starch plasticization with- [24,25]. Then according to the various formulations (Table 1), active compounds were added in the starch-glycerol blend and the humidity rate was adjusted at 10% w/w.…”
Section: Sample Preparationmentioning
confidence: 99%